THE ROLE OF ENDOTHELIN-1, HIF1α, HIF2α IN RETINAL VEIN OCCLUSION - M. V. Budzinskaya; A. V. Shelankova; A. A. Plyukhova; E. I. Rendel (Сибирский научный медицинский журнал, 2019)
The problem of development and course of retinal venous occlusions (RVO) is relevant for today. The etiology of development of the RVO is multifaceted, and has not been fully studied. One of the main reasons for the decline in vision is the development of macular edema. The main problem in the treatment of macular edema is the difficulty in predicting increased visual acuity when disease is combined with retinal ischemia. One of the risk factors for the development of ischemia is endothelial dysfunction, whose important markers are endothelin-1 and hypoxia-inducible factors (HIF1α, HIF2α). Aim of the study was to evaluate the effect of the systemic level of endothelin-1 and hypoxia factors on the course of retinal venous occlusions. Material and methods. Content of the main markers of endothelial dysfunction (endothelin-1, HIF1α, HIF2α) was measured in 137 patients with RVO, among them 59 patients with central retinal vein occlusion and 78 - with central retinal vein branch occlusion. The average age of the patients was 73.35 ± 7.6 years. The level of markers of endothelial dysfunction was determined in serum by ELISA. Results and discussion. A statistically significant increase in endothelin-1 content in patients with optic nerve edema ( p = 0.018) was found. There were no statistically significant data on the effect on the course of the RVO of hypoxia factors HIF1 α and HIF2 α. Conclusion. Assessment of main markers indices of endothelial dysfunction can be used for understanding the etiology of RVO development and the correct tactics of the patients’ treatment forming.